2022
DOI: 10.1016/j.esxm.2022.100545
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Permanent Hair Removal Procedures before Gender-Affirming Vaginoplasty: Why We Should Consider Laser Hair Removal as a First-Line Treatment for Patients Who Meet Criteria

Abstract: Introduction Permanent genital hair removal is required before gender-affirming vaginoplasty to prevent hair-related complications. No previous studies have directly compared the relative efficacy, costs, and patient experiences with laser hair removal (LHR) vs electrolysis treatments. Food and Drug Administration (FDA) oversight of medical devices is poorly understood and commonly misrepresented, adversely affecting patient care. Aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 57 publications
(85 reference statements)
0
20
0
Order By: Relevance
“…Most studies in this review (9/13) focused on transfeminine individuals, 13,[15][16][17][18][21][22][23]25 while only two (2/13) focused on transmasculine individuals. 19,24 Two studies (2/13) included both transfeminine and transmasculine individuals in their study population.…”
Section: Study Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies in this review (9/13) focused on transfeminine individuals, 13,[15][16][17][18][21][22][23]25 while only two (2/13) focused on transmasculine individuals. 19,24 Two studies (2/13) included both transfeminine and transmasculine individuals in their study population.…”
Section: Study Populationsmentioning
confidence: 99%
“…23 Two studies, Berger et al and Yuan et al, investigated the psychosocial outcomes of various methods of preoperative genital hair removal before gender-affirming vaginoplasty. 13,16 Berger et al compared patients who received LHR (n = 11), electrolysis (n = 7) or at-home kits (n = 5), to controls who had not received preoperative genital hair removal (n = 5). They found that postoperative hair growth and recognition of strands of hair on the vaginal dilator upon removal were associated with significantly lower odds of overall satisfaction (odds ratio [OR] 0.07, p = 0.03; OR 0.19, p = 0.02, respectively) and satisfaction with sexual function (OR 0.10, p = 0.002; OR, 0.02, p = 0.01, respectively).…”
Section: Types Of Gender-affirming Dermatology Treatmentsmentioning
confidence: 99%
“…For patients undergoing vaginoplasty either with or without creation of a vaginal canal, preoperative hair removal is required to minimize complications after surgery, including intravaginal irritation, infection, and keratin granulomas [60]. Laser hair removal (LHR) has been demonstrated to require fewer treatments than electrolysis to achieve completion of treatment, which is defined as the absence of regrowth over a period of 2 months [61]. LHR is the most cost-effective therapy for removal of genital hair in patients with pigmented hair.…”
Section: Transgender Carementioning
confidence: 99%
“…67 Laser hair removal may be preferred over electrolysis due to greater efficiency, less pain, better tolerability and decreased cost. 68,69 Intravaginal condyloma, squamous cell carcinoma (SCC) and lichen sclerosis have been reported in neovaginas. 39 As with all surgical procedures, scarring is inevitable, and patients may seek a dermatology review.…”
Section: Dermatological Considerations In Gender-affirming Surgerymentioning
confidence: 99%
“…It is recommended to wait for 3 months following the final hair removal treatment to confirm no hair regrowth before proceeding with surgery 67 . Laser hair removal may be preferred over electrolysis due to greater efficiency, less pain, better tolerability and decreased cost 68,69 . Intravaginal condyloma, squamous cell carcinoma (SCC) and lichen sclerosis have been reported in neovaginas 39 …”
Section: Gender‐affirming Proceduresmentioning
confidence: 99%